Characterization of escherichia coli antibiogram in red hybrid tilapia fish (Tilapia sp.) - Chong, Chee Keong (2011)
This study described antibiogram of Escherichia coli isolated from red hybrid tilapia. E. coli is a well known food pathogen. It is also a common organism found in the human gut and intestinal tract. There are significant data shows that E. coli was exist in tilapia fish. In this present study, bacteria isolated from tilapia using Eosin Methylene Blue agar (EMB agar) and identified through bacterial biochemical tests and conventional identification kit. In the present study, there were 19 types of antibiotic susceptibility were applied. The antibiotics that used in the present study were Compound Sulphonimides, Spiramycin, Fosfomycin, Tetracycline, Kanamycin, Chloramphenicol, Nalidixic acid, Oxytetracycline, Florfenicol, Novobiocin, Doxycycline, Sulphamethaoxazole, Amoxycilin, Colistin sulphate, Oxolinic acid, Erythromycin, Lincomycin, Oleandomycin, and Ampicillin. After the inoculation, the diameters of the bacteria were measured inhibition zone in millimeter (mm). The result of antibiogram of bacteria were interpreted into resistant (R), intermediary sensitive (I), sensitive (S) by refer to Clinical and Laboratory Standards Institute (CLSI) (2006). The present study result showed that 4 out of 19 antibiotics namely Kanamycin (60%), Fosfomycin (85%), Florfenicol (85%) and Chloramphenicol (100%) were sensitive toward E. coll. Hence, the rest of 15 types of antibiotics showed resistant to E. coil with the range 73% to 100%. In present study, it can help to establish database information of antimicrobial that is benefit for future study. Thus, this study provides useful information about application antibiotics used in tilapia farming for public health and consumption awareness.